2007
DOI: 10.1104/pp.107.101691
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Homeostasis and Root Development in Arabidopsis Are Synchronized by the Zinc Finger Transcription Factor ZAT6

Abstract: Phosphorus availability is limited in many natural ecosystems. Plants adapt to phosphate (Pi) deficiency by complex molecular processes. There is growing evidence suggesting that transcription factors are key components in the regulation of these processes. In this study, we characterized the function of ZAT6 (zinc finger of Arabidopsis 6), a cysteine-2/histidine-2 zinc finger transcription factor that is responsive to Pi stress. ZAT6 is induced during Pi starvation and localizes to the nucleus. While the RNAi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
210
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(232 citation statements)
references
References 48 publications
(55 reference statements)
15
210
2
4
Order By: Relevance
“…Disruption of genes involved in transcriptional reorganization or hormone-mediated responses to Pi starvation generally causes a shift in root structure architecture in addition to decreased primary root growth. For example, knockout of PSI transcription factors has been reported to reduce primary root growth with concomitant increases in lateral root and root hair development (Devaiah et al, 2007a(Devaiah et al, , 2007b. Similar results have been obtained with genes that mediate signal transduction in 2Pi Arabidopsis, such as phospholipase Dz1 and Dz2, in which a double knockout exhibited reduced phosphatidic acid levels and altered root structure architecture during Pi starvation (Li et al, 2006).…”
Section: Atpap26 Is Essential For Efficient Acclimation Of Arabidopsisupporting
confidence: 72%
See 1 more Smart Citation
“…Disruption of genes involved in transcriptional reorganization or hormone-mediated responses to Pi starvation generally causes a shift in root structure architecture in addition to decreased primary root growth. For example, knockout of PSI transcription factors has been reported to reduce primary root growth with concomitant increases in lateral root and root hair development (Devaiah et al, 2007a(Devaiah et al, , 2007b. Similar results have been obtained with genes that mediate signal transduction in 2Pi Arabidopsis, such as phospholipase Dz1 and Dz2, in which a double knockout exhibited reduced phosphatidic acid levels and altered root structure architecture during Pi starvation (Li et al, 2006).…”
Section: Atpap26 Is Essential For Efficient Acclimation Of Arabidopsisupporting
confidence: 72%
“…Pi deprivation induces temporal and tissue-specific expression of PSI APase isozymes (Haran et al, 2000;Wu et al, 2003;Zimmerman et al, 2004;Bozzo et al, 2006) and the concomitant downregulation of other APases (Misson et al, 2005). The transcription factors PHR1, WRKY75, and ZAT6 have been implicated in the control of Arabidopsis PSI APases (Rubio et al, 2001;Devaiah et al, 2007aDevaiah et al, , 2007b, while posttranscriptional mechanisms appear to be essential for the up-regulation of the purple APase (PAP) AtPAP26 during Pi stress (Veljanovski et al, 2006;Tran and Plaxton, 2008;Tran et al, 2010b). In contrast, Pi resupply to 2Pi plants rapidly represses PSI APase genes (del Pozo et al, 1999;Mü ller et al, 2004;Veljanovski et al, 2006) while inducing proteases that target PSI-secreted APases (Bozzo et al, 2004b).…”
mentioning
confidence: 99%
“…1E). Taken together, these results suggest that the Cd-tolerant phenotype of xcd2-D might be caused by the estradiol-induced expression of At5g04340, which was previously named as a known gene, ZAT6 (Devaiah et al, 2007).…”
Section: Isolation Of Gain-of-function Xcd2-d Mutantmentioning
confidence: 68%
“…ZAT6 expression has been shown to be regulated by phytohormones (Glazebrook et al, 2003). In addition, it was also found that ZAT6 is involved in regulating root development and low Pi stress responses (Devaiah et al, 2007). Recently, ZAT6 was shown to be involved in regulating responses of plants to pathogen infection, salt, drought, and freezing stresses (Shi et al, 2014).…”
mentioning
confidence: 99%
“…. The literature shows that some previous studies also found harmful effects of phosphite anion on plants grown under low phosphate availability, but no harmful effects have been reported when this anion was applied in plants grown under adequate phosphate availability (TICCONO et al, 2001;VARADARAJAN et al, 2002;LEE et al, 2005;SCHROETTER et al, 2006;DEVAIAH et al, 2007;THAO et al, 2008;MOOR et al, 2009;ÁVILA et al, 2011). However, most of these studies were based in Arabidopsis, vegetables, seedlings, citrus, and some cereals, but there is still little information on the effects of phosphite on leguminous plants, especially on grain yield of leguminous.…”
Section: Resultsmentioning
confidence: 99%